Partnerships In Community Mental Health Nursing And Dementia Care : Practice Perspectives. - Keady, John (McGraw-Hill International (UK) Ltd, 2007)
Provides an account of the complexity, breadth and diversity of community mental health nursing practice in dementia care. This book offers coverage of contemporary issues such as service user involvement, nurse prescribing, younger people with dementia, social exclusion and vulnerability.